Limiting and Enabling Factors of Collective Farmers' Marketing Initiatives: Results of a Comparative Analysis of the Situation and Trends in 10 European Countries - Knickel, Karlheinz; Zerger, Corinna; Jahn, Gundula; Renting, Henk (Journal of hunger & environmental nutrition, 2008)
Linked with the growing power of retailers, European farmers have gradually lost control over supply chains. The resulting pressure on producer prices and the decline in policy support underpin the need for collective action among farmers. Co-operative initiatives in production, processing, and marketing are established in order to improve market access and farm incomes. Changing consumer demands for food safety, quality, and an attractive countryside reinforce these trends. They are interpreted as new opportunities and they lead to an active development of new marketing channels-often through collective action. In this contribution, an overview is provided of the current political, economic, technical, and sociocultural context of newly emerging collective farmers' marketing initiatives. The influence of different contextual settings on producer cooperation in marketing is examined, and key issues are identified related to the promotion and dissemination and the successful performance and continuity of farmers' marketing initiatives. The assessment is based on a comparative analysis of the situation and trends in 10 European countries. Key issues related to the promotion and successful performance of producer cooperation in marketing are identified. The process of the transformation of production into income and employment is seen as critically important in terms of farm family livelihoods and its contribution to a sustainable development of food systems, rural areas, and society at large.